Notas para a caracterização da estação do Puio – Picote, Miranda do Douro - Pinto, Dulcineia C. B. (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This article is the product of a bibliographic research about archaeological findings at Picote during the XIX – XX century and also an archaeological study (ceramics and metal artefacts) of the settlement Puio, located at Picote, Miranda do Douro. This article aims to help to understand the chronological and cultural definition of this important site – Puio - in the history of proto-historic societies in the region.